RAISING GEN Z’S AWARENESS OF FOOD WASTE MANAGEMENT ISSUE - Elmada, Maria Advenita Gita; Ariestya, Angga; Fakhruddin, Irwan (Universitas Pelita Harapan, 2022)
Food waste management is still an unsolved problem in Indonesia, given that public awareness of this is still relatively low. The management of food waste that is not good will have an impact on the preservation of nature and the environment. Gen Z, which is hoped to be the catalyst of the change, is encouraged to understand this issue. In order to raise the awareness of Gen Z on this issue, a webinar was held by a team of lecturers together with a student organization called UMN ECO. Three perspectives are presented: an academician, a food bank organization Garda Pangan representative, and an Instagram eco influencer. A total of 633 university students coming from 16 universities joined the event. The evaluation shows that the students are mostly inspired by this event and eager to know more about food waste management.